HUBUNGAN ANTARA CONSCIENTIOUSNESS DENGAN HASIL BELAJAR BIOLOGI: STUDI KORELASIONAL TERHADAP SISWA KELAS X MIPA DI SMA NEGERI 1 SIMALUNGUN - MARLINDOAMAN SARAGIH (LP2MTBM MAKARIOZ, 2020)
Conscientiousness is exhibited by those who described asdependable, organized, through and responsible. The lack of students conscientiousness make their study result on ecosystem learning of Biology subject became low. This study aims to determine correlation between conscientiousness and study result of biology students at the 1 Senior High School Simalungun in ecosystem subject. This research was held in January-February 2018. The method was used a survey method through correlative studies. The samples were 105 students from Mathematic and Science first grade. The results of normality and homogeneity test showed that data come from normal distribution of populations and homogeneous. The results of hypothesis test showed that there was significant positive correlation between conscientiousness and study result of biology students with a correlation coefficient 0,804 in the equation Ŷ = 5.663 + 0.195X. Conscientiousness contribute to study result of Biology students amounted to 64,69%.